Effect of Application Timing and Concentration of Biosaka on the Growth and Yield of Organic Lowland Rice - Paulus, Jeanne Martje; Demmassabu, Langimanapa S; Najoan, Jemmy; Inkiriwang, Annatje E.B (Journal of Agriculture, 2025)
To achieve sustainable and environmentally friendly agriculture, organic-based rice cultivation techniques utilising local resources are gaining popularity. Biosaka, a plant extract solution, functions as an elicitor with the potential to increase plant productivity. This study aimed to analyse: (1) the single effect of Biosaka application time on the growth and production of lowland rice; (2) the single effect of Biosaka concentration on the growth and production of lowland rice; and (3) the interaction between application time and concentration in influencing the growth and production of lowland rice. The study was conducted in Taratara Dua Village, West Tomohon District, Tomohon City, from April to October 2024. This field study used IR-64 rice varieties and a randomised block design with two factors: application time (5, 10, and 15 days) and concentration (0, 30, and 60 ml/15 L). The variables measured included plant height, number of productive tillers, panicle length, and grain yield. The results showed no interaction between the two factors. Although the application time factor did not significantly affect any variables, the Biosaka concentration significantly affected the number of productive tillers, panicle length, the number of filled and empty grains, and the dry grain yield per plot. Interestingly, this study achieved the highest yield in the control treatment (0 ml/L), with a dry grain yield of 6.19 kg per plot. This indicates that the Biosaka application, at the concentration tested, did not increase rice yield in this study.